PREDIKSI PRODUKSI JAGUNG DALAM MODEL PENYEDIAAN TEPUNG JAGUNG PADA RANTAI PASOK JAGUNG - Dorina Hetharia; M. Syamsul Ma’arif; Yandra Arkeman; Titi Candra S (JURNAL TEKNIK INDUSTRI, 2017)
Corn flour as one of the products made from corn is an intermediate product. This product can be consumed directly, also can be used as raw materials in the food industry, feed industry and other industrial raw materials. In the supply chain system, corn flour industry is a part of the maize supply chain . To maintain the continuity of the flow of raw materials in the supply chain , the industry needs to provide corn flour that meets quantity with good quality according to consumer demand . It is closely related to the supply of corn as a raw material for corn flour. The provision of corn are also closely related to the availability of the amount of corn production obtained from the farmers. This paper discussed about prediction of maize production using artificial neural networks and a statistical forecasting . The input variables of corn production forecast in causal models were land and rainfall, while the output variable was the amount of corn production per month . The forecasting results would be used as input for the corn flour industry